MODEL OF DEVELOPMENT AND DIAGNOSTICS OF COMPUTATIONAL THINKING OF SCHOOLCHILDREN IN TEACHING TRIGONOMETRY AL-FARABI - Akzholova, А.; Kamalova , Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Computational thinking is one of the key concepts of the digital age, a necessary skill of a person of the XXI century. It is a special organization of a person’s thought processes that allows him to analyze and formulate problematic situations in such a way that their solutions can be presented in the form of a sequence of steps carried out using a computer. Today, its development is considered among the most important goals of general education in the field of computer science. It is possible to note other academic disciplines that have the required potential for the development of computational thinking of schoolchildren. There are huge opportunities for its development in the trigonometry of al-Farabi. The purpose of the study: to develop and theoretically substantiate a structural and logical model for the development and diagnosis of this style of thinking in high school students when teaching al-Farabi trigonometry. Results. The structural components of computational thinking and a set of organizational and pedagogical conditions that ensure their effective development in teaching al-Farabi trigonometry are identified and substantiated, taking into account them a structural and logical model of the development and diagnosis of computational thinking in high school students in teaching al-Farabi trigonometry is developed and theoretically substantiated. The model is represented by interrelated and interdependent structural blocks: target, theoretical and methodical, substantive, organizational and evaluative-effective and gives a holistic view of their purposeful impact on the components of computational thinking.